Effect of combining different 10-MDP-containing primers and cement systems on shear bond strength between resin cement and zirconia - Kan Wongkamhaeng; Kopchai Poomparnich; Top Chitkraisorn; Kwanwong Boonpitak; Terawat Tosiriwatanapong (BMC Oral Health)
Abstract Purpose The longevity of zirconia restoration depends upon its esthetic, proper occlusion, marginal adaptation, and restoration retention. This study aimed to investigate the combination of 10-MDP-containing primers between the two commercial systems (Scotchbond Universal Plus Adhesive and Panavia V5) and airborne-particle abrasion on shear bond strength (SBS) between zirconia and resin cement. Methods High translucency zirconia discs were sectioned and sintered according to the manufacturer’s recommendations. The specimens were randomly applied with three different primers (Scotchbond Universal Adhesive, Tooth Primer, and Clearfil Ceramic Primer). Then, each group was bonded with Panavia V5 and RelyX™ Universal resin cements. Airborne-particle abrasion on the zirconia surfaces was also conducted using the manufacturer’s bonding protocol for both resin cements. SBS was analyzed by a two-way ANOVA with Tukey’s adjustment for multiple comparisons (α = 0.05). Results Panavia V5 exhibited the highest SBS with Scotchbond Universal Adhesive (9.66±2.00 MPa) and Tooth Primer (8.47±2.08 MPa), respectively. As-sintered zirconia luted with primers and RelyXTM Universal resin cement exhibited lower SBS than that of Panavia V5. In regard to air-abrasion, air-abraded zirconia luted with Tooth Primer and Panavia V5 exhibited statistically significant higher SBS (29.26±3.26 MPa) than other groups (p<0.0001). Conclusions Combining primers from different adhesive cement systems may significantly enhance the bond strength. Zirconia luted with Scotchbond Universal Adhesive and Panavia V5 achieved the highest bond strength when combined with airborne-particle abrasion.